Evolving Insights into Protein Trafficking to the Multiple Compartments of the Apicomplexan Plastid - PARSONS, MARILYN (2009)
The apicoplast is a relict plastid found in many medically important apicomplexan parasites, such as Plasmodium and Toxoplasma. Phylogenetic analysis and the presence of four bounding membranes indicate that the apicoplast arose from a secondary endosymbiosis. Here we review what has been discovered about the complex journey proteins take to reach compartments of the apicoplast. The targeting sequences for luminal proteins are well-defined, but those routing proteins to other compartments are only beginning to be studied. Recent work suggests that the trafficking mechanisms involve a variety of molecules of different phylogenetic origins. We highlight some remaining questions regarding protein trafficking to this divergent organelle.